The impact of withholding and withdrawal life-sustaining treatment issues on patients with sepsis: a prospective, nationwide, multicenter cohort study - So-yun Kim; Da Hyun Kang; Hyekyeong Ju; Dong Kyu Oh; Su Yeon Lee; Mi Hyeon Park; Chae-Man Lim; Song I Lee; the Korean Sepsis Alliance investigators (Scientific Reports)
Abstract Approximately half of the patients with sepsis require intensive care unit (ICU) management and their mortality rate remains high. The concept of withholding and withdrawal life-sustaining treatment (WWLST) issue was introduced to limit the suffering of critically ill patients. However, little is known about the characteristics and outcomes of WWLST in patients with sepsis. We conducted a nationwide cohort study of adult patients with sepsis prospectively collected from the Korean Sepsis Alliance Database of 20 tertiary referral or university-affiliated hospitals in South Korea between September 2019 and December 2021. Patients were classified according to WWLST issues and characteristics, and their prognoses were compared. Among the 11,981 patients with sepsis included in the study, 4430 (37.0%) had WWLST issues. The WWLST group was older, frailer, and had higher Sequential Organ Failure Assessment (SOFA) scores than the no-WWLST group. The WWLST group had more underlying diseases, including solid tumors (45.2% vs. 30.6%, p < 0.001) and hematologic malignancies (8.0% vs. 5.2%, p < 0.001), than the no-WWLST group. Regarding patient outcomes and interventions in the ICU, the WWLST group used vasopressors (35.4% vs. 32.8%, p = 0.003) more frequently; invasive mechanical ventilation (62.9% vs. 41.9%, p < 0.001) and continuous renal replacement therapy (40.8% vs. 17.6%, p < 0.001) were applied more frequently in the WWLST group than in the no-WWLST group. Logistic regression analysis revealed the factors associated with WWLST group to be old age, low body mass index, higher Charlson comorbidity index, clinical frailty scale, SOFA score, underlying diseases such as solid tumors and hematologic malignancies, invasive mechanical ventilation, and continuous renal replacement therapy. We predicted that the WWLST group would have a fewer ICU admissions and less invasive treatment. However, the admission rate was equivalent, and the percentage of invasive treatment, length of ICU stays, and mortality rate were higher and longer in the WWLST group. In patients with sepsis who have factors related to WWLST, appropriate communication with the patient and their family about WWLST can improve the quality of life and quality of death.